The Effects of the 2004 Hurricane Season on Greenhouse Vegetable Production in Florida - Jeanmarie M. Mitchell; Daniel J. Cantliffe (EDIS)
The 2004 hurricane season proved to be one of Florida's worst. The four hurricanes (Charley, Francis, Ivan, and Jeanne) caused over $2 billion in total agricultural loss. In response, the federal government appropriated $13 billion for emergency assistance, of which Florida received a half billion dollars for agricultural disaster assistance. Many of Florida's producers were eligible for up to $80,000 in aid. Among those who tried but failed to qualify for this aid were greenhouse vegetable producers. Although the greenhouse vegetable industry in Florida is small, it is expanding and the present growers suffered millions of dollars in damages from the hurricanes in 2004. A survey was conducted in March, 2005 to assess both hurricane damages in 2004 and the present status of the greenhouse vegetable industry in Florida. This document is HS1021, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date August 8, 2005.